Challenges and opportunities of age diverse universities: Perspectives from admissions and career services. Issue 3 (3rd July 2022) - Morrow-Howell, Nancy; Galucia, Natalie; Swinford, Emma; Meyer, Tanner
ABSTRACT: Universities are experiencing shifts in age distributions of students, with fewer younger students and an increase in the number of people mid-life and beyond seeking education and job training. Thus, there are strong arguments for universities to embrace opportunities to increase age-diversity on campus. This qualitative study explores the challenges, opportunities, and strategies related to university age-diversity from the perspective of Admissions and Career Services staff from one midwestern university. From focus group data, six subthemes were identified as challenges (fitting in; acclimating; stressors; career concerns; return on investment; and ageism/undervaluing age diversity), three subthemes were identified as assets (intentionality; experienced students; and age diverse educational settings) and eight strategies were recommended to better serve an age-diversity student body (support groups; familial supports; social opportunities; job placement; financial aid; targeted outreach; flexibility in learning; and staff support). This article discusses the benefits and challenges of serving older students from the perspective of staff and administrators and provides action steps for universities to promote age-diversity on campus.